ChemInform Abstract: TADDOL‐Based Phosphorus(III)‐Ligands in Enantioselective Pd(0)‐Catalyzed C—H Functionalizations. Issue 7 (January 2016) - Pedroni, Julia; Cramer, Nicolai
Abstract: Review: [36 refs.